👤

Care este rezultatul acestei operaţii?
5 la puterea 11 -(6×5la puterea 10-2×5 la puterea 10)


Răspuns :

Răspuns:

[tex]\bf {5}^{10}[/tex]

Explicație pas cu pas:

Salutare

[tex] \bf {5}^{11} - (6 \cdot {5}^{10} - 2 \cdot {5}^{10}) = [/tex]

[tex] \bf {5}^{11} - {5}^{10} \cdot(6 \cdot {5}^{10 - 10} - 2 \cdot {5}^{10 - 10}) = [/tex]

[tex] \bf {5}^{11} - {5}^{10} \cdot(6 \cdot {5}^{0} - 2 \cdot {5}^{0}) = [/tex]

[tex]\bf {5}^{11} - {5}^{10} \cdot(6 \cdot 1 - 2 \cdot 1) = [/tex]

[tex]\bf {5}^{11} - {5}^{10} \cdot 4 = [/tex]

[tex]\bf {5}^{10} \cdot( {5}^{11 - 10} - {5}^{10 - 10} \cdot 4) = [/tex]

[tex]\bf {5}^{10} \cdot( {5}^{1} - {5}^{0} \cdot 4) = [/tex]

[tex]\bf {5}^{10} \cdot( 5- 1 \cdot 4) = [/tex]

[tex]\bf {5}^{10} \cdot( 5- 4) = [/tex]

[tex]\bf {5}^{10} \cdot1= [/tex]

[tex] \boxed{\bf {5}^{10}}[/tex]

==pav38==

5¹¹-(6×5¹⁰-2×5¹⁰)=5¹¹-4×5¹⁰=(5-4)×5¹⁰=1×5¹⁰=5¹⁰